The Impact of Green Product Quality on Green Satisfaction Mediated by Green Perceived Value: An Empirical Study of Eco-Friendly Bag Buyers in DKI Jakarta - Michael Christianto Leonardo (International Journal of Social Service and Research, 2023)
This study determines whether Green Product Quality has a simultaneous and partial influence on Green Satisfaction, mediated by Green Perceived Value on eco-friendly bag buyers in DKI Jakarta and surrounding areas. This study employs a quantitative correlational method using primary data and a PLS-SEM with SMARTPLS 3.2.9, a questionnaire as the instrument. The sample size for this study consists of approximately 192 respondents. The sampling technique used is Probability Sampling and Hair formula. Validity and reliability tests, and hypothesis testing using P-Values. These research findings indicate that factors such as the purchase of environmentally friendly bags, both Green Product Quality, Influence Green Satisfaction, with Green Perceived Value as the mediating factor. These results underscore the importance of using eco-friendly products and advocating for the Go Green movement from this point onward to ensure the preservation of the environment and keep the earth healthier.